(untitled) (Journal of Computational Mathematics, 1997)
A conservative difference scheme is presented for the initial-boundary-value problem of a generalized Zakharov equations. On the basis of a prior estimates in L_2 norm, the convergence of the difference solution is proved in order O(h^2+r^2). In the proof, a new skill is used to deal with the term of difference quotient (e_j,k^n)t. This is necessary, since there is no estimate of E(x,y,t) in L_∞ norm.